Obstacle detection using embedded platform – An experimental platform. Issue 1 (February 2021) - Kiran Kumar, D; Athina, Dhanaraju; Shankar, V; Reddy, Navabharat; Vittal, K
Abstract: The research work is about obstacle detection using embedded platform with ultrasonic sensor and servo motor. The working principle of the experimental setup is when embedded board powers then ultrasonic sensor starts detecting the objects which is attached with dc servo motor which is also rotating about 180 degrees. When there is a object or motion caused by any object identified in the path of the ultrasonic sensor vision, it detects the particular object and also calculated the distance in cms and direction view. The embedded board used is arduino controller which controls the ultrasonic sensor and servo motor and the software used to show the graphical representation is Processing IDE which calculates the angle, position of the object, length of the object. The application of this project comes where required different fields of navigation, mapping, positioning the object, and tracking with less cost, more efficient and reliable.